The phenomenon of the language of daily discourse in the modern Iraqi poem: -Pioneer stage - a model - Abbas, Samira Kazem (Al-Adab Journal, 2021)
After technical research into the phenomenon of the daily language of discourse in the modern Iraqi poem of the pioneer poets generation - we reached the most important results of this research, which was based on the technical approach in analyzing the poetic texts in the poems of the pioneer poets, which have a connection with (the language of daily speech), And ended with the following results ....We found that most of the poetic productions of poets throughout the Arab world and the productions of the pioneer poets in Iraq during the period of the forties and fifties were dominated by the romantic character because they inspired a lot of the achievements of the Diwan School, Apollo, and the poets of the Diaspora, by virtue of their communication and the contents of the nature of the poetic experience and its course. The poet’s intellectual and literary orientation plays a prominent role in clarifying his position on language and how he deals with it, because language is affected by the poet’s own vision, so each poet becomes his language and his privacy in dealing with language.The romantic tendency that reached the new Iraqi poet, whether it was from the generation of pioneering poets (Badr Shaker Al-Sayyab, Nazik Al-Malaika, Abdul Wahhab Al-Bayati, Baland Al-Haidari ...) or the generation that followed them, was not that flamboyance and that intensity that the Iraqi poet witnessed since the first decade From this century when it was a great poetic stage with its features, poets and a large number of its poetic productions.The language of poetry has the advantage of being linked to the poet’s attitude towards life and his vision of it, so the effects of romanticism that cast a shadow over the entirety of modern Iraqi poetry during its inception gradually faded away and this fading increases as the poet’s interest in human issues and Arab and Iraqi reality increases.The continuous development of life and its change affect both poetry and the poet. Therefore, the poet’s use of the language of daily discourse is an expression of the reality of daily life that interacts with its various themes, which carry with it the suffering of the Arab people in all parts of the world.The call to use (the language of daily speech) in poetry was not a new call, but rather part of the data of the romantic movement in world literature ..... The Iraqi poet’s orientation to the language of daily speech was not a result of his direct influence in opinions Wordsworth or Elliot, but this is due to the new poet’s awareness and realistic stance that effectively influenced his artistic production, in terms of his connection and interaction with society’s problems and human, social and political issues.The poet’s use of the language of everyday speech does not fall under the cover of the vernacular language as much as it was a language that filtered from eloquent linguistic origins, but with the passage of time it became popular in circulation .... it may glow in some poems to burn with the glow of the inner soul, and in some cases it is like a dim light To get away from that psychological glare.